Performance rating - Barrett, Richard S. (Chicago : Science Research Associates, 1966)
This book is designed as a text and as a handbook of performance rating. It is addressed to two audience and, in a sense is two books bound in one cover
Bibliography: p. 143-161.
ijb, 15/01/2019
Loans
Keywords: Employees - rating of